Signature whistles of the demographic unit of bottlenose dolphins (Tursiops truncatus) inhabiting the Eastern Ligurian Sea: characterisation and comparison with the literature. Issue 1 (1st January 2021) - Terranova, F.; Gnone, G.; Friard, O.; Bellingeri, M.; Giacoma, C.; Favaro, L.
Abstract: Bottlenose dolphins ( Tursiops truncatus ) make extensive use of narrowband whistles with individually distinctive frequency modulations to broadcast their identity: the signature whistles. The acoustic structure of the signature whistles tends to be stable over decades. Therefore, these vocalisations have the potential to be used for monitoring individuals over time. Our study investigated the acoustic structure of the signature whistles of the demographic unit of bottlenose dolphins inhabiting the Eastern Ligurian Sea (Italy), within the Pelagos Sanctuary. Through visual categorisation of spectrograms, we identified 941 whistle contours, 469 of them were classified as signature whistles using the SIGnature IDentification (SIG-ID) method. We further grouped these into 19 different categories based on their stereotyped frequency modulation patterns. To support our categorisation, we used a combination of a visual classification task conducted by six naïve judges and an automated analysis, the principal component analysis. Overall, this study characterises the signature whistles of the demographic unit of bottlenose dolphins inhabiting the Ligurian Sea for the first time. Furthermore, when comparing the acoustic features of these whistles with those of other different demographic units available from the literature, we observed differences in the values of the minimum and maximum frequencies. Considering the critical vessel traffic of our study area, we interpreted these variations in light of the high levels of anthropogenic noise. We recommend further investigations to understand the mechanisms underpinning the acoustic variation of bottlenose dolphins' signature whistles and to elaborate effective management and protection policies for this species.